Treatment delay and clinical outcomes in patients with ST-elevation myocardial infarction during the COVID-19 pandemic. (14th October 2021) - Tokarek, T; Dziewierz, A; Malinowski, K; Rakowski, T; Bartus, S; Dudek, D; Siudak, Z
Abstract: Background: The COVID-19 pandemic negatively affected access to health-care system and timeline of treatment. The fear of contamination might potentially forbear from accessing the emergency system.mFurthermore, pandemic-specific protocols require additional time to prepare medical stuff and catheterization laboratory before procedure. Thus, patients with ST-segment elevation myocardial infarction (STEMI) might be exposed to a longer delay for revascularization and higher risk of mortality. Purpose: The aim of this study was to evaluate treatment delay and clinical outcomes in COVID-19 positive and negative patients with STEMI treated with percutaneous coronary intervention (PCI) during on- and off hours. Methods: All consecutive patients with STEMI treated with PCI and stent implantation between 1st March 2020 and 31st December 2020 were enrolled into analysis. To overcome potential bias related to the non-randomized design a propensity score match (PSM) was used to compare COVID-19 positive and negative patients for both working frames hours. The study group consisted of 877 matched pairs treated during regular hours (everyday 7:00AM-16:59PM) and 418 matched pairs with PCI performed during off-hours (everyday 17:00PM and 06:59AM) in 151 tertiary invasive cardiology centers in Poland (the ORPKI Polish National Registry). Results: After PSM there were no differences between COVID-19 positive and negative patients in baseline characteristics during both on- and off-hours. However, patients diagnosed with COVID-19 were admitted with cardiac arrest more frequently as compared to COVID-19 negative patients during regular working hours (180 (20.5%) vs. 64 (7.30%); p=0.001). There were no differences in radiation doses and total amount of contrast between both groups. Similarly, no differences in rate of periprocedural complications were observed despite of time of intervention, including stroke, access-site-related bleeding, allergic reaction and coronary artery perforation. Furthermore, there were no differences in periprocedural mortality between both groups (on-hours: COVID-19 negative vs. COVID-19 positive: 17 (1.9%) vs. 11 (1.3%), p=0.3; off-hours: COVID-19 negative vs. COVID-19 positive: 4 (1.0%) vs. 7 (1.7%), p=0.5). However, COVID-19 positive patients were exposed to longer time from first medical contact to angiography during both on-hours (133.76 (±137.10) vs. 117.14 (±135.83) [min]; p=0.001) and off-hours (148.08 (±201.56) vs. 112.19 (±138.72) [min]; p=0.003). Time from pain to first medical contact remained similar during both working frame hours (On-hours and off-hours, respectively: p=0.7 and p=0.9). Conclusions: Patients diagnosed with COVID-19 might experience a longer time from first medical contact to revascularization. There was no impact of COVID-19 diagnosis on rate of periprocedural mortality or periprocedural complication, irrespective of time of intervention. System-level changes might be crucial to improve health-care during COVID-19 pandemic. FUNDunding Acknowledgement: Type of funding sources: None.